Multi-component wastewater from finely dispersed impurities treatment intensification - Bosiuk, Alona; Shkop, Andrii; Kulinich, Sergii; Samoilenko, Dmytro; Shestopalov, Oleksii; Tykhomyrova, Tetiana (Ecological Questions, 2024)
The article deals with the intensification of flocculation wastewater treatment from finely dispersed suspended dust particles that are formed in the foundry shop at machine-building productions. The dependence of the floc sedimentation rate and wastewater clarification on solid phase concentration and flocculant flow rate was experimentally researched using model wastewater created by mixing dust and water. The multicomponent impurities of ionic flocculants on the aggregation process impact were experimentally proven, and anionic and cationic flocculants combination high efficiency was shown. The optimal parameters for the wastewater treatment process were established. The best flocculating effect and minimum flocculant consumption were observed at a solid phase concentration of 8-14 g/l. It was established that the most effective aggregate formation process is observed when two flocculants’ types are used simultaneously: anionic A-19 and cationic K-7, not each type separately. Flocculant flow rate experimental and calculated dependences for the wastewater treatment process depending on solid phase concentration and floc sedimentation speed necessary for effective sedimentation have been established. A technological scheme for wastewater treatment from suspended dust impurities that are formed in foundry shop at machine-building enterprise has been developed. The scheme includes: wastewater flocculation; water clarification in a sedimentation tank; and water deironing by aeration with coagulant addition and further filtration. It is proposed to use purified water in enterprise technological cycle that helps to reduce tap water consumption.